The Effect of Chromebook Usage and Learning Interest on Islamic Religious Education Literacy among Elementary School Students - Endang Citra Surya Indah; Choirudin Choirudin; Siti Roudhotul Jannah (Assyfa Journal of Islamic Studies, 2026)
This study examines the influence of Chromebook usage and learning interest on Islamic Religious Education (PAI) literacy among fifth and sixth-grade students at SD Negeri 8 Metro Barat. Employing a quantitative causal-correlational ex post facto design, data were collected from 49 students selected through simple random sampling from a population of 140. Instruments included a 45-item Likert-scale questionnaire validated through expert judgment and reliability testing (Cronbach's Alpha 0.842–0.875). Results from multiple regression analysis revealed three key findings: (1) Chromebook usage significantly and positively affects PAI literacy (β = 0.348, p = 0.009); (2) learning interest significantly and positively affects PAI literacy (β = 0.430, p = 0.001); and (3) both variables simultaneously explain 45.2% of the variance in PAI literacy (R² = 0.452, F = 18.456, p = 0.000). These findings demonstrate that technology integration and students' internal motivation collectively enhance religious literacy. The study contributes theoretical insights into technology-based PAI learning models and offers practical recommendations for schools, teachers, and policymakers to optimize Chromebook utilization and foster learning interest in Islamic education.